(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article contains features of gastroduodenitis in children with saline diathesis. Recently, in conditions of ecological trouble, there has been a significant increase in the combined pathology of the gastrointestinal tract with diseases of the urinary system, namely, clinically pronounced oxalate-calcium crystalluria in combination with gastritis and gastroduodenitis. It has been proven that changes in the ecology of the external environment contribute to the development of calcium oxalate crystalluria, which affects the clinical, morphological, and functional characteristics of chronic gastroduodenitis in children.